Penurunan Kinerja Pegawai Karena Work-Family Conflict dan Stres Kerja - Widnyani, Desi Cipta; Benni Kusyana, Dewa Nyoman (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the effect of work family conflict and work stress on employee performance both partially and simultaneously. This research was conducted at the Bali Regional Settlement Infrastructure Office with a population of 165 employees according to the established population criteria, namely married men and women. The number of samples was determined as many as 62 people using the Slovin Formula and the sample selection was carried out using proportionate sampling. Respondents' answers to the questionnaire given were then tested for validity and reliability using SPSS software. After the instrument is declared valid and reliable, it is continued with the classical assumption test and finally the hypothesis test with multiple linear regression. The results of the study prove that work family conflict has a negative and significant effect on employee performance and work stress has a significant negative effect on employee performance. Simultaneously, work family conflict and work stress have a significant effect on employee performance.